THE INFLUENCE OF CONTENT MARKETING ON PURCHASE INTENTION - Wahyuni, Dewi Kamalia; Raharja, Sam’un Jaja; Kostini, Nenden (Journal of Management Small and Medium Enterprises (SMEs), 2026)
The purpose of this study is to analyze the influence of content marketing on purchase intention among Instagram followers of @MasaRemajaCollective. This study uses a quantitative descriptive-verification approach. The population of this study was 10,400 Instagram followers of @MasaRemajaCollective. The sample was taken using the Slovin formula with a margin of error of 10%, resulting in a minimum sample size of 100 respondents. The sampling technique used probability sampling with simple random sampling. Data analysis used simple linear regression, a normality test, a linearity test, and a hypothesis test. The results showed that content marketing implemented by @MasaRemajaCollective has a positive and significant influence on the purchase intention of the audience on Instagram. Keywords: Content Marketing; Purchase Intention; Instagram